2021
DOI: 10.1055/a-1386-5826
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Maculopathy in Mitochondrial DNA A3243G Mutation: A Case Series of Six Patients

Abstract: Background The mitochondrial DNA (mtDNA) A3243G point mutation encompasses a heterogenous group of disorders including mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS), maternally inherited diabetes and deafness (MIDD), and, rarely, chronic progressive external ophthalmoplegia (CPEO). Regardless of the clinical phenotype, a specific retinopathy has been associated with the presence of this mitochondrial DNA mutation. We present six female patients exhibiting retinopathy of the A3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…We do not agree with the statement that "all mitochondrial disorders (MIDs) are strictly maternally inherited" [1]. In addition to the maternal trait, MIDs can follow an autosomal dominant, autosomal recessive, or X-linked trait of inheritance.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…We do not agree with the statement that "all mitochondrial disorders (MIDs) are strictly maternally inherited" [1]. In addition to the maternal trait, MIDs can follow an autosomal dominant, autosomal recessive, or X-linked trait of inheritance.…”
mentioning
confidence: 57%
“…
With interest we read the article by Kaisari and Borruat about six female patients with maculopathy due to the mtDNA variant m.3243A>G [1]. Visual acuity ranged from 1/60 to 10/10, visual field abnormalities ranged from minimal decreased sensitivity to absolute central scotoma, and three patients exhibited variable degrees of characteristic perimacular and peripapillary retinal pigment epithelium abnormalities, with mottled dye autofluorescence and retinal pigment epithelium atrophy, and deposits on optic coherence tomography [1]. The study is appealing but raises a number of concerns.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of the study is that the diagnosis of KSS was not genetically confirmed. [ 1 ] KSS is commonly due to single mitochondrial DNA (mtDNA) deletions and rarely due to the variants m. 3243A >G[ 2 ] or m. 3249G >A. [ 3 ] Because ophthalmoparesis together with retinopathy may occur in several other syndromic and non-syndromic mitochondrial disorders,[ 4 ] it is crucial that the diagnosis KSS is substantiated by documentation of an appropriate pathogenic genetic defect.…”
mentioning
confidence: 99%